From State Control to Competition: German Higher Education Transformed - Wolter, Andra (Canadian Journal of Higher Education, 2004)
Although there have been several cycles of debate and reform on higher education since World War II, the most recent proposals, some implemented and others under consideration, are by far the most far reaching and consequential of the period. Most aim at resolving the conflict between the ideal of the Humboldtian model of an elite research university, and the demand for an open, accessible, and differentiated system of higher education that takes into account the pivotal role of higher education in the modern world and in a democratic and pluralistic society. Forces and factors at work in other countries have affected the timing and dynamics of system transformation, but the unification in the early 1990s of the two German states, in which higher education had very different structures and mandates, has played a great role in the matter.